Balloon Pulmonary Valvuloplasty in patients with Congenital Valvular Pulmonary Stenosis - Sharma, R; Rajbhandari, R; Limbu, Y; Singh, S; Bhatt, YKD; KC, MB (Nepalese Heart Journal, 2013)
Background Congenital valvular pulmonary stenosis (PS) accounts for most of the etiology of PS, and constitutes about 5 to 10% of all congenital heart disease. Balloon Pulmonary Valvuloplasty has become the choice of treatment for valvular PS since the first series reported by Kan et al in 19824 and has almost replaced surgical valvotomy in pediatric patients. The purpose of this study was to investigate the immediate results of balloon valvuloplasty in patients with congenital valvular pulmonary stenosis. Method We analyzed hemodynamic data of 122 patients who underwent balloon pulmonary valvuloplasty (ages14days- 50 years mean 25 years). Single-balloon technique was used. Right ventricle systolic pressure and pulmonary valve Peak-to-peak systolic pressure gradient were recorded before and after balloon dilatation of pulmonary valve. Result Right ventricle systolic pressure decreased from 128±44.9 to 60±24.9 mmHg (p <0.001) and pulmonary valve peak-to-peak systolic pressure gradient decreased from 89±38.6 to 45 ± 22.4 mmHg (p <0.001). No major complication or mortality was noted. Conclusion Balloon pulmonary valvuloplasty is a safe and effective treatment for patients with congenital valvular PS. DOI: http://dx.doi.org/10.3126/njh.v9i1.8340 Nepalese Heart Journal Vol.9(1) 2012 pp.7-9ca